A Highly Efficient Self‐Healing Elastomer with Unprecedented Mechanical Properties. Issue 23 (12th April 2019) - Zhang, Luzhi; Liu, Zenghe; Wu, Xueli; Guan, Qingbao; Chen, Shuo; Sun, Lijie; Guo, Yifan; Wang, Shuliang; Song, Jianchun; Jeffries, Eric Meade; He, Chuanglong; Qing, Feng‐Ling; et al.
Abstract: It is highly desirable, although very challenging, to develop self‐healable materials exhibiting both high efficiency in self‐healing and excellent mechanical properties at ambient conditions. Herein, a novel Cu(II)–dimethylglyoxime–urethane‐complex‐based polyurethane elastomer (Cu–DOU–CPU) with synergetic triple dynamic bonds is developed. Cu–DOU–CPU demonstrates the highest reported mechanical performance for self‐healing elastomers at room temperature, with a tensile strength and toughness up to 14.8 MPa and 87.0 MJ m −3, respectively. Meanwhile, the Cu–DOU–CPU spontaneously self‐heals at room temperature with an instant recovered tensile strength of 1.84 MPa and a continuously increased strength up to 13.8 MPa, surpassing the original strength of all other counterparts. Density functional theory calculations reveal that the coordination of Cu(II) plays a critical role in accelerating the reversible dissociation of dimethylglyoxime–urethane, which is important to the excellent performance of the self‐healing elastomer. Application of this technology is demonstrated by a self‐healable and stretchable circuit constructed from Cu–DOU–CPU. Abstract : A dimethylglyoxime–urethane (DOU)‐based polyurethane elastomer self‐heals immediately at room temperature and shows world‐record strength and toughness. Cu(II)DOU coordination bonds greatly strengthen the materials while enhancing the dynamics of the DOU bonds to facilitate self‐healing. This material design reconciles the contradictory properties of mechanical robustness and self‐healing efficiency, providing a powerful new strategy to create high‐performance self‐healing materials.